INVESTIGATING STUDENTS’ PERSPECTIVES ON THE USE OF TIKTOK AS AN INSTRUCTIONAL MEDIA IN DISTANCE LEARNING DURING PANDEMIC ERA - Nurul Afidah; Novi Kumala Sari; Hanifah Hanifah (Universitas KH. A. Wahab Hasbullah Tambakberas Jombang, 2021)
Abstract This study aims to investigate on students’ perspective on the use of TikTok Application as supplementary instructional media during pandemic session. 20 students of English Department Student at UNWAHA were voluntary to take part in this descriptive study. Employing questionnaire was carried out to obtain data related to their opinion. The researcher collects the data through questionnaire. Then, the researcher selects and identifies the data. After selecting the data, the researcher displays those data into good sentences. 3) After displaying data, the conclusion is drawn. This questionnaire is analyzed by using descriptive statistics The findings revealed that students at UNWAHA second-semester give positive attitudes towards introducing TikTok as video aids into EFL classroom teaching meanwhile using it as an English learning strategy out of class. Also, they stated that TikTok is expected to be used as instructional media in speaking class.